Occupational skin diseases: a cross-sectional survey analysis - Ineke Winda Ferianasari; Reza Yuridian Purwoko; Evy Aryanti; Azizah Boenjamin; Silvan Saputra; Asmail Asmail (International Journal of Public Health Science (IJPHS), 2026)
Occupational skin diseases (OSDs) are among the most common occupational diseases worldwide, yet scientific data in Indonesia remain limited. This issue is important to study because workers across various sectors frequently encounter wet work, detergents, and chemical exposure. The present study aimed to assess individual and occupational risk factors associated with skin complaints/symptoms on the hands and forearms within the past 12 months and to test the feasibility of a simple prediction model in the Indonesian context. A cross-sectional study was conducted among 46 workers participating in health screening. Predictor variables included age, sex, type of occupation, length of employment, frequency of handwashing, shift work, and exposure status. Analysis was performed using Firth’s logistic regression with reporting of odds ratios (OR), 95% confidence intervals (CI), and significance testing. Model performance was evaluated using the Hosmer-Lemeshow test, AUC/ROC, and Nagelkerke’s pseudo-R². The prevalence of skin complaints reached 56.5%. Female workers had a 17-fold higher risk compared to males (OR = 17.20; 95% CI: 1.79-164.77; p = 0.014). The prediction model demonstrated good performance (AUC = 0.90; Hosmer-Lemeshow p = 0.307; Nagelkerke R² = 0.60). Female sex was identified as an important determinant of OSD in this population. The simple prediction model proved feasible for risk screening and could serve as a basis for prevention programs focusing on exposure control in Indonesia. Further studies with larger samples are needed to strengthen evidence across occupational categories.